PREDICTING THE IMPACT OF A FCC TURBO EXPANDER ON PETROLEUM REFINERIES - Fermoselli, N. E. G. (Revista de Engenharia Térmica, 2010)
Implementing a turbo expander connected to a fluid catalytic cracking (FCC) unit in order to produce power from flue gas has already become a common practice in oil refineries worldwide. Despite of recovering energy which used to be wasted in an orifice chamber, the implementation of expander and its skids still requires high investment, which often begins with a third-stage cyclones installation to enhance flue gas cleanness. Moreover, machine and also pipes need to be made with special materials in order to resist high temperatures and erosion. Hence, there are some items to be checked before start up a turbo expander to ensure the return on investment will reach expectations, keeping in mind that its ability to extract energy from flue gas changes widely depending on FCC operational conditions. Then, the aim of this paper is to provide the analysis of one stage turbo expander which is fed with flue gas from partial combustion FCC unit and installed with isolation valves, highlighting some points which deserve special attention before start up this type of machine. It brings together some approaches to provide valuable information about a turbo expander, particularly when it is not running yet, including the results to a hypothetical case and the sequence of calculus that can be done without using any special software applied for: • To estimate real energy generation through the turbo expander as a function of FCC feed; • To check the leaks effect; • To predict the impact of turbo expander on carbon monoxide boiler, due to a fall in temperature of the expanded flue gas; • To calculate the appropriate amount of extra supplementary gas required to be burned in the flue gas boiler in order to keep the production of steam stable; • To analyze the moisture of the flue gas so that it may predicts condensation when hot gas comes into contact with the cold duct, after opening isolation valves; • And finally, how turbo expanders fit in cleaning development mechanism to get certified carbon credits.